Construction of Ag–ZnO/cellulose nanocomposites via tunable cellulose size for improving photocatalytic performance. (15th March 2021) - Shi, Chun; Zhang, Lili; Bian, Huiyang; Shi, Zhengjun; Ma, Jinxia; Wang, Zhiguo
Abstract: The Ag–ZnO/cellulose nanocomposites with tunable structure and properties was fabricated and used as an effective photocatalyst for degrading methyl orange (MO) dye. The structure and properties of the Ag–ZnO/cellulose nanocomposites were regulated by the cellulose fiber size via different times of grinding treatment. The morphologies of ZnO NPs changed from flower-like to flaky with the decrease of diameter of cellulose fiber from 130 nm to 42 nm, and loading amounts of ZnO and Ag NPs on photocatalyst increased from 56.12% to 57.46% and 5.28%–6.54% respectively. The finer fibrils provided a more uniform network compared with coarse fibers, which is benefit for stable distribution of ZnO and Ag nanoparticles (NPs) and facile separation from wastewater. The Ag–ZnO/cellulose nanocomposites, prepared from cellulose fiber with grinding treatment of 30 times, exhibited homogeneous three-dimensional cellulose network with specific surface area of 40.64 m 2 /g and possessed excellent photocatalytic activities and reusability for MO degradation. This work provided a novel approach to control the morphology of ZnO by tuning cellulose size, for improving photocatalytic activities and recovery efficiency of Ag–ZnO/cellulose nanocomposites. Graphical abstract: This work introduced a method to control the structure and properties of cellulose nanocomposites by regulating the fiber size through grinding. Cellulose was selected to be the substrate to disperse ZnO NPs, and Ag NPs were used to enhance its photocatalytic performance through the inhibition effect of Ag on the recombination of electron and hole in ZnO photocatalysis process. Image 1 Highlights: The Ag–ZnO/cellulose catalyst was fabricated based on tunable cellulose fiber sizes. The morphologies of ZnO were varied with different cellulose fiber sizes. The catalyst exhibited highly photocatalytic performance and recyclability. The mechanism of photocatalytic activities was investigated by scavengers method.